Cobweb weavers - Miller, Jake, 1969- (New York : PowerKids Press, 2004)
Describes the anatomy, web-making, food, reproduction, enemies, and usefulness to humans of cobweb weavers, a family of spiders that includes the harmless house spider and the poisonous black widow and Australian redback spiders.
Includes index.
6.5
3-6
Keywords: Cobweb weavers -- Juvenile literature; Cobweb weavers; Spiders; Cobweb weavers; Spiders